Immunohistochemical distribution of Plexin A4 in the adult rat central nervous system - Claire-Anne Gutekunst; Eric N Stewart; Robert E Gross (Frontiers Media S.A., 2010)
PlexinA4 is the latest member to be identified of the plexin A subfamily, critical transducers of class 3 semaphorin signaling as co-receptors to neuropilins 1 and 2. Despite functional information regarding the role of PlexinA4 in development and guidance of specific neuronal pathways, little is known about its distribution in the adult central nervous system (CNS). Here we report an in depth immunohistochemical analysis of PlexinA4 expression in the adult rat CNS. PlexinA4 staining was present in neurons and fibers throughout the brain and spinal cord, including neocortex, hippocampus, lateral hypothalamus, red nucleus, facial nucleus and the mesencephalic trigeminal nucleus. PlexinA4 antibodies labeled fibers in the lateral septum, nucleus accumbens, several thalamic nuclei, substantia nigra pars reticulata, zona incerta, pontine reticular region, as well as in several cranial nerve nuclei. This constitutes the first detailed description of the topographic distribution of PlexinA4 in the adult CNS and will set the basis for future studies on the functional implications of PlexinA4 in adult brain physiology.